Study guides

☆☆

Q: What is 5x - 3y -7x plus 2y plus 3x?

Write your answer...

Submit

Related questions

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2

5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10

3x-3y+7z

5x-2y+3z-2x-y-4z=3x-3y-z

2x + 4y - 5x + 3y = 7y - 3x

If you mean: 2y+5x = 13 and 2y-3x = 5 then x = 1 and y = 4

6x - y

In its simplest form: 2y -5x

It is: 6x-5y simplified

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

3x + 7y

If you mean: 5x+2y+x-3y then it is 6x-1y

8x+1y+-15 if you are combining variables.

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5

-5(x + 2y) -3x + 8y + 5 = -5x -10y -3x + 8y + 5 = -8x -2y + 5

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

5x+3y = -2 3y = -5x-2 y = -5/3x-2/3 Slope: -5/3

Multiply the bottom equation by -1

By rearranging and combining similar terms. For example, 3x + 5x = (3+5)x = 8x.

3x+2y=20 5x-2y=1 (3x+2y) + (5x-2y)= 20+1 3x+5x= 21....... 8x=21.........x=2 5/8 Subsitute x=3(2 5/8)+ 2y=20........... 7 7/8 +2y=20.........2y= 20- 7 7/8....... y=6 1/16

-2x+2y

For 5x+y=1, you would subtract 5x from each side, so you would get y=1-5x For 3x+2y=2, you would subtract 3x from each side, and then divide by 2. 2y=2-3x y=1-(3/2)x

No.

I understand this to be 4x + 3y - 5x + 2y. -x + 5y